Staging Atmospheres: Editorial introduction to the first volume - Chloé Déchery; Martin Welton (Ambiances)
This special issue of Ambiances seeks to address issues raised by the emerging theatrical paradigm within international scholarship on atmosphere and ambiance. On the one hand, the issue seeks to investigate why the theatre seems to present itself as such an acute example of what Thibaud (2015) has termed the ‘affective tonality’ of aesthetic experience for scholarship that does not necessarily attend to the study of performance per se. On the other hand, it concerns what, in turn, the practice and study of theatre has to learn from enquiries across a range of other disciplines in which features of theatre and the theatrical as aesthetic, spatial and/or social generators of atmospheres have been regularly deployed by scholars in architecture, geography and philosophy. What might greater insight into the production and reception of theatre’s atmospheric conditions lend to enquiries that draw upon it analogically and/or in exemplary terms? How can the staging of atmospheres within theatre and associated practices offer concrete examples and methods to broader concerns for sociocultural, political, and ecological climates? Similarly, what lessons should theatre and performance take from the considerable efforts within the atmosphere studies to address its own affects, aesthetics, and environments?